THE EFFECT OF JOB SATISFACTION, ORGANIZATIONAL COMMITMENT AND COMPENSATION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AT EXPEDITIONARY SERVICE COMPANY - Nurjayanti, Desy; Riyanto, Setyo (Dinasti Publisher, 2022)
Organization Citizenship Behavior (OCB) is one of the positive organizational attitudes that can be raised with variable Job Satisfaction, Organizational Commitment and Compensation benefit. This study aims to analyze the effect of Job Satisfaction, Organizational Commitment and Compensation benefit towards Organization Citizenship Behavior at PT Pos Indonesia. The data sources come from primary and secondary data. Primary data is taken from distributing questionnaires, while secondary data is from literature books, journals, and company data. Data was distributed to 243 employees and use random sampling technique. This research methodology uses descriptive and quantitative methods using Smart PLS to analyze several theoretical concepts. The result showed that the variable Job Satisfaction, Organizational Commitment and had a positive and significant effect on Organization Citizenship Behavior, Compensation benefit did not positively and significantly affect the Organizational Citizenship Behavior (OCB).